Microarray analysis of lncRNA and mRNA expression profiles in patients with Legg-Calve-Perthes disease - Wang, Shangyu; Zhong, Haobo; Ze, Renhao; Hong, Pan; Li, Jin; Tang, Xin (Frontiers in Pediatrics, 2022)
Background: The etiology and underlying pathogenic mechanisms of Legg-Calve-Perthes disease (LCPD) still remain unclear. A disruption of blood supply to the femoral head, producing ischemic necrosis, appears to be the critical pathological event. The lncRNAs play crucial roles in many biological processes and are dysregulated in various human diseases. However, its expression profiles and the potential regulatory roles in the development of LCPD have not been investigated. Methods: In this study, differentially expressed lncRNA and mRNA of Legg-Calve-Perthes disease patients were profiled. Several GO terms and pathways that play important roles in the regulation of vascular structure, function or coagulation were selected for further analysis. The lncRNA -mRNA interacting networks in LCPD tissues were constructed to identify novel potential targets for further investigation. Results: The microarray analysis revealed that 149 lncRNAs and 37 mRNAs were up-regulated, and 64 lncRNAs and 250 mRNAs were down-regulated in LCPD tissues. After filtering, we finally found 14 mRNAs and constructed an mRNA-lncRNA interacting network. Through the analysis of the interaction network, we finally found 13 differentially expressed lncRNAs, which may be implicated in the pathogenesis of LCPD. These mRNAs/lncRNAs were further validated with qRT-PCR. Conclusion: The findings of this study established a co-expression network of disease-related lncRNAs and mRNAs which screened out from the concerned G.O. terms and Pathways, which may provide new sights for future studies on molecular mechanisms of LCPD.